The Development of Hadith Studies in Indonesia in the 20-21 AD Century - D. Indah Syifana (STIU Al-Mujtama Pamekasan, 2021)
Hadith as the second source of Islamic teachings is very important to study. However, in Indonesia the study of hadith in its development is inversely proportional to the progress of other Islamic sciences. This delay took place over a long period of time, starting from the beginning of the entry of Islam to Indonesia until the end of the 20th century AD. Meanwhile, in modern times the study of hadith has progressed rapidly, both in terms of quantity and quality. However, the progress of this era also raises several problems regarding the authenticity and understanding of the hadith itself. This article will discuss the development history and characteristics of hadith studies in Indonesia. The development of hadith will never be separated from the role of the scholars at that time, therefore in this article the author also describes the figures and works produced in the scientific field of hadith.